Examining spatial variation in soil solutes and flowpaths in a semi-arid, montane catchment - Gregory, Reece B.; Bush, Sidney A.; Sullivan, Pamela L.; Barnard, Holly R. (Frontiers in Water, 2022)
Biogeochemical properties of soils play a crucial role in soil and stream chemistry throughout a watershed. How water interacts with soils during subsurface flow can have impacts on water quality, thus, it is fundamental to understand where and how certain soil water chemical processes occur within a catchment. In this study, ~200 soil samples were evaluated throughout a small catchment in the Front Range of Colorado, USA to examine spatial and vertical patterns in major soil solutes among different landscape units: riparian areas, alluvial/colluvial fans, and steep hillslopes. Solutes were extracted from the soil samples in the laboratory and analyzed for major cation (Li, K, Mg, Br, and Ca) and anion (F, Cl, NO2, NO3, PO4, and SO4) concentrations using ion chromatography. Concentrations of most solutes were greater in near surface soils (10cm) than in deeper soils (100cm) across all landscape units, except for F which increased with depth, suggestive of surface accumulation processes such as dust deposition or enrichment due to biotic cycling. Potassium had the highest variation between depths, ranging from 1.04 mg/l (100 cm) to 3.13 mg/l (10 cm) sampled from riparian landscape units. Nearly every solute was found to be enriched in riparian areas where vegetation was visibly denser, with higher mean concentrations than the hillslopes and fans, except for NO3 which had higher concentrations in the fans. Br, NO2, and PO4 concentrations were often below the detectable limit, and Li and Na were not variable between depths or landscape units. Ratioed stream water concentrations (K:Na, Ca:Mg, and NO3:Cl) vs. discharge relationships compared to the soil solute ratios indicated a hydraulic disconnection between the shallow soils (<100 cm) and the stream. Based on the comparisons among depths and landscape units, our findings suggest that K, Ca, F, and NO3 solutes may serve as valuable tracers to identify subsurface flowpaths as they are distinct among landscape units and depth within this catchment. However, interflow and/or shallow groundwater flow likely have little direct connection to streamflow generation.